Stories of Backlash in Interviews With Survivors of Intimate Partner Violence Against Women in Sweden - Wemrell, Maria (Violence against women, 2023)
Despite high gender equality ratings, Sweden shows a high prevalence of intimate partner violence against women (IPVAW). Suggested factors underlying this apparent paradox include backlash effects against women's empowerment. This study explores stories of backlash in interviews with 23 IPVAW survivors in Sweden. Thematic analysis identified categories of narrative segments referring to phenomena provoking violence; the victims’ resources, agency, breaking with gender norms and resistance, and the partner's feelings of subordination, while case-centered narrative analysis pointed to divergences between how these categories appear in the stories. The study underscores the complexity of links between gender (in)equality and IPVAW in Sweden.